Analisis dan Perancangan Sistem Informasi Pembelian dan Penjualan Obat (Studi kasus pada Apotek Amanah) - B41112099, HENDRA DUTA BRYANATA (Jurnal Kajian Ilmiah Akuntansi Fakultas Ekonomi UNTAN (KIAFE), 2017)
ABSTRACTAnalysis and Design of Purchasing and Sales Information System (Case Study on Amanah ApothecaryÂ Apotek Amanah is located on Jl. Tani Makmur No. 2B Pontianak, West Kalimantan. This Apothecary began to be established on November 12, 2015. systems that are running on the Amanah Apothecary is now using a computerized system. Unfortunately in this system there are still some weaknesses. Therefore the author wants to provide a recommendation of a better information system design that can cope with these problems. This study aims to determine the existing purchasing and sales information system at the Amanah Apothecary. Then to know what factors that could be the cause of ineffectiveness of the system. And after that design a new purchasing system to solve the problems faced earlier. And the last objective of this research is the implementation or application of the system designed by the author.The method used in this study is Qualitative, which is intended to describe and analyze events, social activities, attitudes, beliefs, perceptions, thoughts of individuals individually or in groups. Some descriptions are used to find the principles and explain which leads to inference.With the new system design it is expected to overcome the existing problems in Amanah Apothecary and can facilitate the performance of the Amanah Apothecary to be more effective. Keywords: System, Apothecary, Medicine, Purchase, Sales.